The Meaning of the Steps is in Between: Dancing and the Curse of Compliments - Tamisari, Franca (The Australian journal of anthropology, 2000)
This paper shows how Yolngu dancing embodies statements about being-in-the-world and being-with-others and, from a performance perspective based on participation, explores the sensuous and affective nature of intercorporeality. By focusing on virtuosity and the practice of the ‘curse of compliments’, the paper argues that the meaning of Yolngu dancing is between the steps, between the performers and other participants in a ceremony—in the empathic space one enters through dancing. Empathy, both in the context of Yolngu performance and of engagement in fieldwork, is thus a modality of co-presence and co-presencing, an encounter at a level of intensity which opens the way to an ever-deepening involvement with others.